Quality of Services for Making Family Card (KK) in Department of Population and Civil Registration Iin Garut Regency through the Pandu-Online Application - Fidowaty, T; Ramdani, H; Kandias, M R N (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
To realize the welfare of the community, the Garut district government performs a service function. The government is required to provide quality services as part of public services based on law number 25 of 2009 concerning public services. One of the services provided by the Garut district population and civil registration service is the service of making a family card which contains data about the composition, relationships and number of family members. The purpose of this research is to find out the Quality of Service for Making Family Cards through the online guide application at the Garut Regency Population and Civil Registration Service in serving the community.The research method used in this research is descriptive with a qualitative approach. Data collection techniques used in this study through library research, field studies, namely observation, interviews and documentation. The informant determination technique is using a purposive technique. The conclusion of research is showing that there are still limited facilities to support the service of making a Family Card through the online guide application at the Garut Regency Population and Civil Registration Office, such as internet support which is not fast enough. The capability of the apparatus is not optimal in handling crashes/disturbances in the online guide application system. The conclusion this research is If the quality of family card services is good, the population in Indonesia will be accurate. the impact of this research is to become a concern for the government and become knowledge in government science for future researchers